Deep Brain Stimulation of the Nucleus Basalis of Meynert for Parkinson's Disease Dementia: A 36 Months Follow Up Study. Issue 6 (27th July 2022) - Cappon, Davide; Gratwicke, James; Zrinzo, Ludvic; Akram, Harith; Hyam, Jonathan; Hariz, Marwan; Limousin, Patricia; Foltynie, Thomas; Jahanshahi, Marjan
ABSTRACT: Background: Degeneration of the nucleus basalis of Meynert (NBM) and cortical cholinergic dysfunction are hallmarks of Parkinson's disease dementia (PDD). There is no effective therapy for PDD. Deep brain stimulation of the NBM (NBM‐DBS) has been trialed as a potential treatment. Objective: Our primary aim was to evaluate the sustained tolerability of NBM‐DBS in PDD, and its impact on global cognition, behavioral symptoms, quality of life and caregiver burden and distress. Second, we aimed to determine whether baseline measures of arousal, alertness, and attention were predictive of the three year response to NBM‐DBS in PDD patients. Methods: Five of the six PDD patients who completed the baseline assessment participated in a 3 year follow up assessment. We assessed the participants after three years of NBM‐DBS on the Mini Mental State Examination, Dementia Rating Scale‐2, Blessed Dementia Rating Scale, Neuropsychiatric Inventory, and the SF36. Results: The five patients showed varying trajectories of cognitive decline, with two showing a slower progression over the three‐year follow‐up period. A slower progression of decline on global cognition was associated with higher baseline accuracy on the Posner covert orienting of attention test, and less daytime sleepiness. Conclusions: Whether slower progression of cognitive decline in two patients was in any way related to individual variability in responsiveness to NBM‐DBS requires confirmation in a larger series including an unoperated PDD control group. Higher accuracy in covertly orienting attention and better sleep quality at baseline were associated with better cognitive outcomes at 36 months assessment. These results require validation in future studies with larger samples.